[PHS5] Dampak Volume Berita Figur Publik dan Peringatan Hari Kanker terhadap Volume Pencarian Kanker di Indonesia: Studi Analisis Google Trend - Syahru Agung Setiawan; Mardiah Suci Hardianti (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Purpose: Indonesia has grown huge number of internet users thus becomes novel health promotion target in digital era. As Google Trends allows observing public health seeking information rapidly along with our concern towards public cancer interest which is affected by public figure news and cancer campaign, we studied cancer search oscillations in Indonesia in relation to both factors.Methods: Search queries comprised of cancer topics (Kanker; Kanker Darah; Leukemia; Kanker Paru; Kanker Getah Bening; Kanker Nasofaring), public figures news (Ani Yudhoyono; Arifin Ilham; Adira Taista; Anak Denada; Istri Indro; Sutopo; Valentino Nahak), and cancer awareness days (Hari Kanker Sedunia; Hari Kanker Anak; Hari Kanker Payudara) were generated to get their search volumes from 2018 to first trimester of 2019 subsequently grouped them into 3 main topics (cancer, public figure news, and cancer awareness day). Trend-to-trend analysis among main topics is evaluated using Pearson’s correlation, multiple linear regression, and cross-correlation.Result: Strong correlation is evidenced between cancer and public figure search (r = 0,752; p= <0,001) but lower in cancer awareness day (r=0,296; p = 0,017). Multivariate analysis shows significant impact of public figure, secular trend, and cancer awareness day on cancer search volume in Indonesia (R2 = 0,646; p < 0,001).Discussion: This study demonstrates strong influence of public figures on cancer-seeking despite temporary for about 4 weeks with public figure search leads 1 week before evidenced cancer search. Positive yet lower effect of cancer campaign requires some improvement towards this intervention.Conclusion: Compared with cancer campaign, public figure news would ‘blow-up’ most Indonesian internet users towards cancer searching significantly but temporarily, which demands health promoter to maximize this ‘golden period’ to give informative and reliable cancer content in conjunction to fight cancer hoax, or possibly cooperate with cancer survivor public figures for promoting public awareness towards cancer.